Investigação de técnicas para o acompanhamento do desgaste de um par engrenado utilizando tribologia e análise da resposta dinâmica processada via função densidade probabilidade Beta - Silva, Erickson Fabiano Moura Sousa [UNESP] (2015)
This work investigates the use together of two techniques to detect faults in toothed gears. These techniques are based on the vibration monitoring and the oil lubricant analysis. Gears are the parts more likely to present faults in many mechanical systems due to its dynamic characteristics, such as the cyclic load applied to the meshing teeth. The main faults in gears are the so-called pitting and scuffing, where the tooth profile (involute) is heavily affected. Moreover, such change in the tooth profile lead to non-uniform angular speed ratio, decrease the efficiency of the system (gear pairs) and increase the dynamic effects which may lead to severe damages in the tooth. Hence, signal processing techniques have been developed to aid in the detection of gear faults at their early stages. It is already known that the dynamic behaviour of a mechanical system changes when its characteristics are affected, such as the presence of fault. As result, the response of such system can be used to detect a fault at its early stage. This is where the vibration monitoring is based on. However, in order to investigate and develop techniques based on the vibration analysis, the physical understanding of the system, in here a gear pair, is required. In this work a technique based on the beta probability density function is investigate to detect in which tooth of a meshing gear the fault is occurring, and also monitoring its evolution along time. Furthermore, the analysis of debris in the lubricant oil (tribology) is also used to reinforce the presence of a fault in the system. Although the later show that the lubricant analysis is quite efficient in detecting faults at its early stages, this technique does not pinpoint in which tooth the fault is occurring. In this case, the beta function complements the lubricant analysis being one of the objectives of this work. A special test rig has been designed and ...